A Novel Pale-Yellow Coat Color of Rabbits Generated viaMC1R Mutation With CRISPR/Cas9 System - Xiao, Ning; Li, Hongli; Shafique, Laiba; Zhao, Shanshan; Su, Xiaoping; Zhang, Yu; Cui, Kuiqing; Liu, Qingyou; Shi, Deshun (Frontiers in Genetics, 2019)
Melanocortin 1 receptor (MC1R) is considered as one of the major genes in mammalian coat color that provides the variation in research. MC1R promotes activated the synthesis of eumelanin, and loss-of-function and leads to the widespread distribution of phaeomelanin. In attempt to alter the coat color of Lianshan black rabbit and explore the regulation mechanism of MC1R on the formation of coat color, we generated MC1R knock-out (KO) rabbits via co-injection of Cas9 mRNA and dual SgRNAs into rabbit zygotes. Finally, we got two MC1R mutated rabbits with novel coat color, showing a lighter and softer yellow phenotype than wild yellow rabbits in the nature. Each MC1R KO rabbit contained different modification types including large fragment deletion, of which the longest deletion was more than 700 bp. And one of them was confirmed that the coat color was changed from original black to pale yellow by knocking out MC1R gene.We speculated that the MC1R pathway was completely disturbed and dysfunctional MC1R might lead to changes in the expression of some downstream genes, resulting in a pale yellow phenotype. The underlying molecular mechanism of this observation remains to be explored. Our study is the first time reported the novel coat color rabbits by disruption of MC1R gene via CRISPR/Cas9. It demonstrated that rabbit MC1R gene plays critical role in determination of coat color, and the coat color can be changed by disruption of MC1R gene. The targeted rabbits with the novel coat color by gene editing can be as a model to study the mechanisms of MC1R gene function.